2018
DOI: 10.1111/1755-0998.12769
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the marine medaka Oryzias melastigma

Abstract: Marine medaka (Oryzias melastigma) is considered to be a useful fish model for marine and estuarine ecotoxicology studies and has good potential for field-based population genomics because of its geographical distribution in Asian estuarine and coastal areas. In this study, we present the first whole-genome draft of O. melastigma. The genome assembly consists of 8,602 scaffolds (N50 = 23.737 Mb) and a total genome length of 779.4 Mb. A total of 23,528 genes were predicted, and 12,670 gene families shared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 60 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…For instance, Malmstrøm and colleagues [ 13 ] reported the genome of 66 teleost species, in which 48 genomes showed between 33 and 84% (complete and fragmented) of the genes present in the Actinopterygii library. A combination of short and long read provides, however, a higher detection of BUSCO scores, and should be pursued in the near future [ 29 , 30 , 31 , 32 ]. To further determine the genome completeness, we mapped the de novo assembled liver transcriptome against the genome with Blat [ 33 ].…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…For instance, Malmstrøm and colleagues [ 13 ] reported the genome of 66 teleost species, in which 48 genomes showed between 33 and 84% (complete and fragmented) of the genes present in the Actinopterygii library. A combination of short and long read provides, however, a higher detection of BUSCO scores, and should be pursued in the near future [ 29 , 30 , 31 , 32 ]. To further determine the genome completeness, we mapped the de novo assembled liver transcriptome against the genome with Blat [ 33 ].…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…2 ), which mapped 90.7% (713 Mb) of the reference genome assembly sequence onto the genetic map ( Table 3 ). Although all SNP markers were extracted by the alignment of RAD sequences against the reference genome of marine medaka (Kim et al 2018), the number of anchored markers were lower than anticipated. Many markers in the LGs were excluded from the integrating process due to inconsistency between the genetic map and reference assembly, indicating possible errors in marker order and/or de novo assembly.…”
Section: Discussionmentioning
confidence: 98%
“…RAD-tag extraction and genotyping were performed with Stacks v.1.47 software (http://creskolab.uoregon.edu/stacks/) (Catchen et al 2011). The sequence reads were aligned to the available reference genome (GCF_002922805.1; Kim et al 2018 ) using GSnap (https://www.gvst.co.uk/gsnap.htm) with default parameters (-t 30 –n 1 –m 5 –i 2), which were converted to BAM files. All RAD-tags catalog from the parental samples were extracted by Stacks using the ref_map.pl pipeline with the parameters –m10 and -P 3 and genotyping was called by the parameters of minimum number of 5 reads to call a homozygous genotype, a minimum minor allele frequency of 0.1 to call a heterozygote, and a maximum minor allele frequency of 0.05 to call a homozygote.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, plummeting cost and numerous advancements in sequencing technologies and bioinformatic algorithms have made assembling of highly sophisticated genomes possible with relatively low cost. Currently, one draft genome of O. melastigma has published based on a reference genome assistant assembling approach [25]. The published genome of O. melastigma was generated using Illumina reads from several libraries, including three paired-end libraries (PE400, PE500 and PE800) and four MP (mate-pair) libraries (MP2kb, MP5kb, MP10kb and MP20kb).…”
Section: Introductionmentioning
confidence: 99%
“…The published genome of O. melastigma was generated using Illumina reads from several libraries, including three paired-end libraries (PE400, PE500 and PE800) and four MP (mate-pair) libraries (MP2kb, MP5kb, MP10kb and MP20kb). Then scaffolds and pseudochromosomes were assembled based on alignment to the chromosomes of Japanese medaka (Oryzias latipes) genome [25]. However, studies have shown that the usage of short Illumina sequencing reads for wholegenome sequencing is a cost-efficient way, but it can also omit the most exciting and perhaps evolutionarily important genome regions [26].…”
Section: Introductionmentioning
confidence: 99%